Feedbacks between fire and patches of woody vegetation in tropical grasslands and savannas :Powerpoint - Groen, T.A. (University of Twente, 2020)
This lecture presents: Rapid increase in woody cover in many savannas; What mechanism can cause rapid woody increase ?; Feedbacks between fire and patches of woody vegetation; Simple model; Effect of fire; Feedbacks between fire and patches of woody vegetation; Kruger National Park: burning plots; Clustering: measuring distances between trees.